Leveraging agricultural mechanization and service expansion to drive rural economies - Aravindakshan, Sreejith; Parupalli, V.L. Bharathi; Kafil Uddin; Hoque, Muhammad Arshadul; Saiful Islam; Calvert, Owen D.; Krupnik, Timothy J. (TAFSSA, 2024)
Mechanization not only lessens the burdens of manual labor but also empowers rural communities by creating avenues for economic upliftment and poverty alleviation. At the intersection of prosperity and resilience, agricultural mechanization emerges as a catalyst for transformative change. By harnessing the efficiency and precision of modern machinery, farmers can achieve higher yields and unlock new avenues of income generation. Moreover, mechanization fosters climate resilience by enabling timely planting and harvesting, mitigating the adverse impacts of climatic variability, and safeguarding agricultural livelihoods against nature's uncertainties. By leveraging technology, agricultural mechanization provides a multifaceted solution, including rural employment generation and opportunities for farmer income, to tackle Bangladesh's agricultural challenges, paving the way for a sustainable and prosperous future.